Characterizations of Continuous Fractional Bessel Wavelet Transforms - Srivastava, Hari M.; Mishra, Kush Kumar; Upadhyay, Santosh K. (MDPI, 2022)
In this paper, we present a systematic study of the various characteristics and properties of some continuous and discrete fractional Bessel wavelet transforms. The method is based upon the theory of the fractional Hankel transform. © 2022 by the authors.
Keywords: Bessel function; continuous fractional Bessel wavelet transform; discrete fractional Bessel wavelet transform; fractional Hankel convolution; fractional Hankel transform